TATA KELOLA AGAMA DALAM KEHIDUPAN SOSIAL: (Suatu Kajian Normatif, Dialogis dan Koncergensif) - Mustafa, Muhtadin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2022)
Humans cannot be separated from religion in society's social life. Based on this explanation, the aim of this research is how religious adherents open up space for dialogue based on tolerance. The methodology in this research is qualitative using library research, while the approach taken is a normative, dialogic, and convergence approach. The results of this research show that Islamic-Christian relations have lasted for centuries amidst various tensions and harmonization of life. However, they realize that religion is a necessity that is believed to provide a guarantee of safety and happiness. Therefore, every believer must be open and willing to dialogue with other people